CYP2C19 Polymorphism and Clinical Outcomes among Patients of Different Races Treated with Clopidogrel：A Systematic Review and Meta-Analysis - 牛璇 毛玲 黄燕 苏冉杰 李剑勇 高原 夏远鹏 贺权威 王梦嵽 李嫚 邹丽 缪小平 胡波 (Journal of Huazhong University of Science and Technology. Medical sciences, 2015)
Several studies have investigated the association between CYP2C19 polymorphism and clinical outcomes of patients treated with clopidogrel, but few have noticed the difference in association between Westerners and Asians. We searched MEDLINE, EMBASE and Cochrane Library database and conducted a systematic review and meta-analysis. Thirty-six studies involving 44 655 patients with coronary artery disease（CAD） treated with clopidogrel were included, of which more than 68% had undergone percutaneous coronary intervention（PCI）. The primary outcome of our interest was the recurrence of major adverse cardiovascular events（MACE） in those CAD patients. Firstly, we found that the distribution of reduced-function CYP2C19 allele varied between Westerners and Asians. Among Asians, 1 and 2 reduced-function CYP2C19 mutant allele carriers accounted for 42.5% and 10%, respectively. While among Westerners, 1 and 2 reduced-function CYP2C19 mutant allele carriers accounted for 25.5% and 2.4%, respectively. Secondly, the impact of CYP2C19 polymorphism on clinical outcomes of patients treated with clopidogrel varied with races. Among Asians, only 2 reduced-function CYP2C19 mutant allele carriers had the reduced effect of clopidogrel. And the reduced effect was significant only after the 30 th day of treatment. While among Westerners, both 1 and 2 reduced-function CYP2C19 allele carriers had the reduced effect, and it mainly occurred within the first 30 days. Thirdly, the safety of clopidogrel was almost the same among races. Reduced-function allele non-carriers had higher risk for total bleeding but did not have higher risk for major bleeding. It is suggested that CYP2C19 polymorphism affects the efficacy of clopidogrel differently among Westerners and Asians.